Indigenous Prehistoric Pottery And Technology In Peninsular Malaysia. - Chia, Stephen Ming Soon

(untitled)
Pottery represents one of prehistoric man's most tangible products.Its universal occurrence and its relatively imperishable nature has made it an important "tool" for archaeologists to reconstruct past cultures and also to use it as an indicator of a cultural stage i.e. the "Neolithic".